Design of a switchable phase‐modulated metasurface with wide modulation bandwidth in S band. Issue 7 (30th April 2022) - Guo, Tiantian; Chen, Qiang; Liu, Taolin; Zheng, Yuejun; Ding, Liang; Fu, Yunqi
Abstract: This article presents a switchable phase‐modulated metasurface (PMM) whose reflection phase can be modulated between two states using PIN diodes. The PMM is composed of a switchable surface loaded with four PIN diodes in each unit cell, as well as a ground plane and an air spacer. The reflection phase can be modulated when the PIN diodes are switched between two states (ON and OFF). Theoretical analysis indicates that the phase‐modulation bandwidth is determined by the thickness of the PMM. The phase‐modulation bandwidth with a phase difference of 180 ± 37° achieves 2.6–4.25 GHz and a fractional bandwidth of 48.2%.